The impact of digital marketing on customer satisfaction in dental tourism in Serbia - Ostojić, Bojana; Bajramović, Dženis; Cvjetković, Milena (Hotel and Tourism Management, 2025)
Purpose – The study aims to examine the impact of digital marketing on customer satisfaction and loyalty in dental tourism, focusing on Serbia. Key digital marketing elements analyzed include website quality, social media presence, online reviews, price transparency, and the promotion of additional services, alongside customer satisfaction factors such as trust, engagement, risk perception, and value perception. Methodology – The research was conducted through an online survey with 220 respondents who used dental services in Belgrade and its surroundings. The collected data were analyzed using correlation and regression analysis to determine the relationship between digital marketing factors and user satisfaction and loyalty. Findings – The results indicate that online reviews and website quality have the most significant positive impact on customer trust and satisfaction, while social media presence and the promotion of additional services have a moderate influence. Price transparency emerged as a crucial factor shaping customer perceptions of dental services. Implications – The findings highlight the importance of digital marketing in dental tourism and can help dental clinics develop more effective marketing strategies. Future research could explore the long-term effects of digital marketing and conduct comparative analyses of different dental tourism markets.